Formação e processamento de imagens de ultrassom - Jen John Lee (2010)
Acoustic imaging allows the inspection and analysis of biological tissue and others materials in a non-destructive way, what is desired to improve the knowledge and to insure the quality about the analyzed object.This work was motivated by the lack of quantitative methods of analysis, usually based on qualitative diagnoses from experienced inspectors, what can vary, as well the lack of imaging systems where the pure RF signal of ultrasound could be acquired.Quantitative methods of analysis are highly desired when developing new piezoelectric materiais, biomedic phantom models and new diagnoses methods.It was developed in this work: an electrical-mechanic scanning system synchronized with the ultrasound acquisition device and image formation by different methods that allowed the development of an algorithm to prepare and to segment these images and different soft tissue phantom models.It was noticed that a statistic Wiener filter, even with no advantages for qualitative analysis of an image, improved the automatic segmentation of it.